January 24, 2020 Sivrice-Elazığ (Türkiye) Earthquake: The Seismic Assessment of the Earthquake Territory, Geotechnical Findings and Performance of Masonry Buildings - Dedeoglu, Ibrahim Ozgur; Yetkin, Musa; Calayir, Yusuf; Erkek, Hakan (Springer Int Publ Ag, 2023)
On January 24, 2020, an 6.8 magnitude (Mw) earthquake struck the Sivrice district of Elazig province in south-eastern Turkiye. The earthquake, which occurred in the East Anatolian Fault Zone (EAFZ), affected many structures. In particular, most of the masonry buildings close to the epicenter were severely damaged or destroyed and the earthquake resulted in 41 fatalities. This paper aims to provide information on the tectonic characteristics of the EAFZ, the seismic characteristics of the earthquake territory and the general characteristics of the main shock. Another purpose of this paper is to reveal the damage caused by the earthquake to the masonry buildings in rural areas through post-earthquake field observations. As a result of the field observations, the types of damage seen in masonry structures are poor workmanship and binder damages, in/out of the plane mechanism, damages due to the absence of lintels or insufficient lintel length, weak load-bearing walls damage, corner damages and multi-leaf walls damages. The most important reason for the damage to the structures is the lack of engineering services and not being constructed in accordance with earthquake codes. In addition, considering the damage to the masonry buildings as a result of the field studies, some retrofitting methods are presented for strengthening existing masonry buildings with low seismic performance against future earthquakes.
Keywords: January 24 2020 Sivrice-Elazig earthquake; East anatolian fault zone; Masonry buildings; Field investigation; Earthquake performance